2017
DOI: 10.1097/dss.0000000000000924
|View full text |Cite
|
Sign up to set email alerts
|

Microneedling: A Comprehensive Review

Abstract: Microneedling appears to be an overall effective and safe therapeutic option for numerous dermatologic conditions. Larger and more randomized controlled trials are needed to provide greater data on the use of microneedling for different dermatologic conditions in different skin types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
125
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 50 publications
1
125
2
2
Order By: Relevance
“…Another adjunctive treatment is microneedling or mesotherapy, which creates small channels in the skin to deliver small amounts of topical drugs intradermally [ 56 , 58 , 88 ]. The skin punctures induced by microneedling can also stimulate a beneficial wound-healing response with fewer side effects compared to conventional resurfacing procedures [ 89 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another adjunctive treatment is microneedling or mesotherapy, which creates small channels in the skin to deliver small amounts of topical drugs intradermally [ 56 , 58 , 88 ]. The skin punctures induced by microneedling can also stimulate a beneficial wound-healing response with fewer side effects compared to conventional resurfacing procedures [ 89 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dissolvable but also permanent, MNs have been www.advancedsciencenews.com www.advtherap.com demonstrated to be well tolerated and easy to use. [51][52][53] MN-based insulin delivery systems are reviewed in the paper of Chen et al, which reports on the full chain from the materials to the commercial devices available on the market. [49,50] In both cases, the self-administration and painlessness of MNs greatly improved the efficacy of treatments.…”
Section: Translational Challengesmentioning
confidence: 99%
“…Exhaustive reviews on dermatological studies involving humans can also be found in the recent literature. [51][52][53] MN-based insulin delivery systems are reviewed in the paper of Chen et al, which reports on the full chain from the materials to the commercial devices available on the market. [54] Finally, the most relevant paper published in the field describes the results of a phase 1 clinical trial study on human vaccination against influenza.…”
Section: Translational Challengesmentioning
confidence: 99%
“…Microneedling, a term familiar to most dermatologists today, has continuously evolved since its inception in the early twentieth century. The technique of microneedling is built upon non-pathogenic puncturing of the skin with micro-sized needles, thereby stimulating the underlying cells to increase the production of growth factors and the vital dermal ingredient, collagen (Aust et al 2008 ; Hou et al 2017 ). The use of microneedles is painless relative to the conventional hypodermic needles since they cannot penetrate the dermis layer (Azmana et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%